Student motivations for studying criminology: A narrative inquiry. (July 2022) - Trebilcock, Julie; Griffiths, Clare
The number of students studying criminology at university has significantly increased. Yet, criminology students have been all but ignored in research, despite being key stakeholders and ambassadors in the criminological enterprise. Drawing on the analysis of 12 in-depth interviews, we explore why students are motivated to study criminology and how these motivations are linked to their past experiences and future aspirations. Using a narrative inquiry, three types of stories emerged through our analysis: stories about (1) building on existing interests, (2) understanding the 'self', and (3) securing 'justice' and 'helping' others. The stories students tell about their exposure to 'crime' help motivate their decision to study criminology, while their engagement with the discipline, enables them to make sense of these previous experiences and of themselves.